MARKETING STRATEGY FOR 109 PILLOW THROUGH TIK TOK LIVE (STUDY AT PT SEMOGA BERKAH SUKSES GROUP: Strategi Pemasaran 109 Pillow Melalui Tik Tok Live (Studi pada PT Semoga Berkah Sukses Group - Mochammad Gilang Ramadhani; Poppy Febriana (Journal for Technology and Science, 2024)
The whole world knows that there has been a pandemic phenomenon for 2 years in all countries including Indonesia, this has made some people's habits change, including in buying a product or shopping. The existence of social media is now not only used as a means of entertainment, but as a modern marketing tool used by many businesses to reach buyers on a large scale. This study aims to analyze what Social Commerce Strategy is carried out by PT. Semoga Berkah Sukses Group or more familiarly known as 109 Pillow Official through the Tik Tok Live feature to increase sales. This study uses a qualitative method approach with an analytical descriptive model. Data collection was carried out through observation, documentation studies and interviews with 109 Pillow owners and their Live Hosts. The results of this study indicate that consistently live streaming by implementing several strategies optimally is the biggest cause of increased sales.